Functional significance of the sex chromosomes during spermatogenesis - Hu, Yueh-Chiang; Namekawa, Satoshi H (Reproduction (Cambridge, England), 2015)
Mammalian sex chromosomes arose from an ordinary pair of autosomes. Over hundreds of millions of years, they have evolved into highly divergent X and Y chromosomes and have become increasingly specialized for male reproduction. Both sex chromosomes have acquired and amplified testis-specific genes, suggestive of roles in spermatogenesis. To understand how the sex chromosome genes participate in the regulation of spermatogenesis, we review genes, including single-copy, multi-copy, and ampliconic genes, whose spermatogenic functions have been demonstrated in mouse genetic studies. Sex chromosomes are subject to chromosome-wide transcriptional silencing in meiotic and postmeiotic stages of spermatogenesis. We also discuss particular sex-linked genes that escape postmeiotic silencing and their evolutionary implications. The unique gene contents and genomic structures of the sex chromosomes reflect their strategies to express genes at various stages of spermatogenesis and reveal the driving forces that shape their evolution.Free Chinese A Chinese translation of this is freely available at http://www.reproduction-online.org/content/149/6/R265/suppl/DC1.Free Japanese A Japanese translation of this is freely available at http://www.reproduction-online.org/content/149/6/R265/suppl/DC2.